2015
DOI: 10.1161/atvbaha.115.306362
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Vascular Network Assembly From Diabetic Patient-Derived Induced Pluripotent Stem Cells

Abstract: Objective In diabetics, hyperglycemia results in deficient endothelial progenitors and cells, leading to cardiovascular complications. We aim to engineer three-dimensional (3D) vascular networks in synthetic hydrogels from type-1 diabetes (T1D) patient-derived human induced pluripotent stem cells (hiPSCs), to serve as a transformative autologous vascular therapy for diabetic patients. Approach and Results We validated and optimized an adherent, feeder free differentiation procedure to derive early vascular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 52 publications
3
65
0
Order By: Relevance
“…These endothelial cells could undergo morphogenesis and assemble into 3D networks when cultured in engineered hyaluronic acid hydrogels or in response to low oxygen in vivo and could incorporate into developing vasculature in zebrafish. 76 Similar results were also obtained in another study where human iPS cells derived from somatic tissue could differentiate into both endothelial cells and pericytes which were fully functional both in vivo and in vitro. 77 In investigation into the mechanisms of iPS cell differentiation, Chen et al 78 found that miR-199b is involved in endothelial differentiation.…”
Section: Embryonic Stem Cells/induced Pluripotent Stem Cellssupporting
confidence: 80%
See 1 more Smart Citation
“…These endothelial cells could undergo morphogenesis and assemble into 3D networks when cultured in engineered hyaluronic acid hydrogels or in response to low oxygen in vivo and could incorporate into developing vasculature in zebrafish. 76 Similar results were also obtained in another study where human iPS cells derived from somatic tissue could differentiate into both endothelial cells and pericytes which were fully functional both in vivo and in vitro. 77 In investigation into the mechanisms of iPS cell differentiation, Chen et al 78 found that miR-199b is involved in endothelial differentiation.…”
Section: Embryonic Stem Cells/induced Pluripotent Stem Cellssupporting
confidence: 80%
“…75 Human iPS cells derived from patients with type 1 diabetes mellitus display a similar differentiation efficiency when compared with iPS cells derived from healthy donors. 76 These patient-derived iPS cells can differentiate into endothelial lineages expressing typical endothelial markers and with functional capabilities of lectin binding, acetylated low-density lipoprotein uptake, tube formation in matrigel, and response to TNF-α. These endothelial cells could undergo morphogenesis and assemble into 3D networks when cultured in engineered hyaluronic acid hydrogels or in response to low oxygen in vivo and could incorporate into developing vasculature in zebrafish.…”
Section: Embryonic Stem Cells/induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Chan and colleagues 17 were recently able to generate early vascular cells with high portions of vascular endothelial cadherin-positive cells from inducible pluripotent stem cells from patients with type 1 diabetes. These cells formed three-dimensional vascular networks in vitro and incorporated into the vasculature in a zebra fish model.…”
Section: Novel Pathways For Vascular Cell Perturbations In Diabetesmentioning
confidence: 99%
“…Those tissues with lower relative O 2 levels will exhibit shallower gradients 38 . We have demonstrated that insights into the role of varying O 2 during tumor growth, vascular development 42 , and angiogenesis 38,43 can be acquired using these hydrogels.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, Gel-HI hydrogels provide a system that more closely mimics the native regenerative niche than do other culture systems. For example, our laboratory has shown that early vascular cells derived from induced pluripotent stem cells of diabetic patients can generate lumenized networks in hypoxic Gel-HI hydrogels, indicating their responsiveness to hypoxic pathways 42 .…”
Section: Introductionmentioning
confidence: 99%